Effect of tree-crop combinations and nitrogen levels on herbage yield of sacred basil (Ocimum sanctum L.) grown in agrihorti-silvi-pasture system in mid hill Himalayas - Verma, K.S.; Thakur, N.S.; Rana, R.C. (Indian Journal of Agroforestry, 2020)
Investigations on effect of tree-crop combinations and nitrogen levels on growth and herbage yield of Ocimum sanctum L. were carried out during 2004-2005 and 2005-2006, in experimental farm of Department of Silviculture and Agroforestry, Dr. Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh (India). O. sanctum was grown in association with Prunus persica (Peach), Grewia optiva, Morus alba and Setaria sphaceleta. The distinctive tree-crop combinations were, Peach + Grewia + Setaria + O. sanctum, Peach + Morus + Setaria + O. sanctum, Peach + Setaria + O. sanctum, Grewia + Setaria + O. sanctum, Morus + Setaria + O. sanctum and O. sanctum as sole crop. Three nitrogen doses applied to O. sanctum were 40, 80 and 120 kg/ha. Maximum plant height (90.70 cm) and leaf area (14.62 cm2/leaf) of O. sanctum was recorded under tree-crop combination Peach+Morus+Setaria. However, leaf area index (LAI) was higher (2.77) for the plants grown under Peach+Grewia+Setaria. Nitrogen dose of 120 kg/ha produced tallest plants (90.96 cm) with leaf area of 15.84 cm2/leaf and LAI 3.16. The total herbage yield was not affected by tree-crop combinations however, it was maximum (5.56 t/ha) under Peach+Morus+Seteria. Plant growth attributes i.e. plant height, leaf area, LAI along with herbage yield increased significantly with the increase in N dose.